Simulação da viabilidade econômica e avaliação de taxas de arraçoamento para tilápia-do-nilo (Oreochromis niloticus) em bioflocos - Villes, Valesca Schardong (2019)
The objectives of this study were to evaluate the effects of feed rates on performance, body composition, biochemical and oxidative parameters of fish in biofloc system (BFT) and to simulate factors that interfere with the economic viability of tilapia breeding. In article 1, a 28-day experiment was carried out with 144 tilapia juveniles (12.06 ± 0.16g), 12 fish per tank in a BFT system, composed of 12 polypropylene tanks (microcosmos, 30 L) and a macrocosm. (1000 L). The animals were fed three times a day (8, 12 and 18 hours) with extruded feed (36% CP) at the rates of 2, 4, 6 and 8% of biomass per day. Influence of feeding rate on fish performance was observed, where the maximum estimated rate was 4%. Apparent feed conversion worsened in proportion to the increase in feed supply. The crude protein of the centesimal composition was higher at the 8% level and the dry matter showed growth according to the feed rate. Lipid contents were higher at 6% and 8% of feedstocks. Fish fed at lower rates had better oxidative parameters due to the consumption of biofloc phenolic compounds. In article 2 a BFT project was simulated, with 12 greenhouses (containing 415m3 tanks each), being housed 55 tilapia/m3 , with estimated feed conversion of 1.2: 1, final weight of 800 g and commercialization price of R$ 4.65. Indicators such as Net Present Value (NPV), Payback, Internal Rate of Return (IRR), Discounted Payback, Profitability Index and sensitivity analyzes were analyzed. The project proved to be economically viable, since the return on investment is between the fourth and fifth year, with NPV of R$ 59,792.94 and IRR of 17%, with high implementation cost and operating costs. Variations in commercialization price, feed conversion and stocking density can have a major influence on the profitability of the enterprise. Feed and energy are the items that most affect the viability of the system, as they represent 70% and 21.79% of operating costs, respectively. In conclusion, in the BFT system, the 4% feeding rate for tilapia juveniles is recommended and the enterprise is economically executable among the characteristics defined in the work, with the highest operating costs defined by the ration and electricity.